FEATURES OF THE INTRODUCTION OF A MODULAR LEARNING SYSTEM IN HIGHER EDUCATION (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
In this article, the concept of a modular learning system, the purpose, features of a modular learning system, special attention is paid to the components of the module. It also covers the introduction of a modular learning system in higher education in Uzbekistan. The content of modular learning technology in the given higher education system serves to achieve a deeper understanding of the essence.